Understanding Buddhism through Pali in India and Thailand - Upender Rao (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2017)
Pali plays a vital role in the history and culture of India. It preserves the Indian culture in a systematic way. Hence an attempt of understanding the Indian culture without Pali cannot fulfil the complete purpose. In fact Pali was an important source for understanding ancient Buddhist culture and philosophy which are integral part of Indian culture. In ancient India there were Buddhist universities and people from many countries used to visit India to learn the Indian culture including Buddhist philosophical expositions. Indian languages and literatures were highly influenced by Pali language and literature.